Application of USLE and GIS tool to predict soil erosion potential and proposal land cover solutions to reduce soil loss in Tay Nguyen - Ha, Nguyen Manh; Dung, Nguyen Van; Ngoc, Hoang Huyen (Vietnam Journal of Earth Sciences, 2014)
Soil erosion is the main reason of the soil degradation in the mountain and plateau areas in Vietnam. The soil in Tay Nguyen is losing productivity because of erosion. This research was used the Universal Soil Loss Equation (USLE) was established by Wischmeier W.H and Smith D.D, together with Geographical Information System (GIS) tool and soil profile in the fields to establish soil erosion potential map and assess soil loss level in each part of Tay Nguyen. The soil erosion level I was occupied 79,10% of the total area; the soil erosion level II was held 16,57% of the total area; the soil erosion level III was occupied 2,78% of the total area, and each or the level IV and V weren’t over 1% of the total area. In Tay Nguyen can be applied many methods for protecting soil avoid erosion. That are using land cover (including vegetation and cultivate method) as forest reproduction with native plants; using agro-forestry models in the sloping land; planting the suitable vegetation or crop; and ensuring that slope land has dense vegetation cover during the rain reason